Lumbar Myelography in a Crab-Eating Raccoon (Procyon cancrivorus) - Minto, Bruno Watanabe [UNESP]; Santo Silva, Paloma do Espirito [UNESP]; Tertuliano Marinho, Paulo Vinicius; Zani, Carolina Camargo; Ferreira Teles, Pedro Henrique [UNESP]; Werther, Karin [UNESP]; Lima, Tiago Barbalho [UNESP]; Canola, Julio Carlos [UNESP] (Univ Fed Rio Grande Do Sul, 2016)
Background: The Crab-eating raccoon (Procyon cancrivorus) is a nocturnal mammal and lives in savannah, but loss of their natural habitat makes increase cases of traffic accidents on the roads. A growing number of wildlife are treated in veterinary hospitals, but we have some limitation about the correct interpretation of the diagnostic test, specially because, even the tests were not described. Myelography is a radiographic technique indicated for compressive lesions of the spinal cord that are not seen on plain radiographs. The present report aims to describe, for the first time, a lumbar myelogram performed in a paraplegic crab-eating raccoon after it suffer a traffic trauma. Case: A free living adult, 8-kg, female raccoon was presenting acute paraplegia and swelling in the region of the left humerus was referred at veterinary hospital. The patient was alert and aggressive, good body score and no signs of active bleeding. The animal temper did not allow approaching it; therefore, physical and neurological examinations were not feasible. The raccoon was tranquilized (1.6 mL of nilperidol (R) intramuscular), anesthetized (propofol, dose-effect intravenous) and tracheal intubation to provide oxygen and the patient was monitored continuously, followed by referred for radiology service. The simple radiograph showed a complete transverse fracture in the humerus and compression fracture of the twelfth thoracic vertebra (T12), being then indicated the myelographic examination to assess the extent of spinal cord compression. The lumbar region was surgical antisepsis prepared. After being properly positioned in lateral decubitus with moderate cranial flexion of the trunk, the patient underwent lumbar puncture by inserting a spinal needle between the 5th and 6th intervertebral lumbar spaces. The spinal needle was introduced slightly caudolaterally to the spinous process of the 6th lumbar vertebra and cranioventrally directed at an angle of 45 degrees. Then, the needle was pierced through the ligamentum flavum and the dura mater while, concomitantly, we observed the tail moving and the cerebrospinal fluid (CSF) output while the contrast was injected. The contrast iohexol (300 mg/mL) was used at a dose of 0.25 mL/kg. Immediately after the slow injection of contrast (approximately 3 min), radiographs were taken in the latero-lateral and ventrodorsal projections to identify the location of the spinal cord disorder. The extension degree of the lesion was evidenced by the reduction of the contrast column width at the location of instability. The patient was referred for surgical decompression and stabilization. Discussion: In cases where paraplegia results from trauma, spinal radiography and myelography are important means to confirm the diagnosis, specially the extent of the compression and prognosis. There are certain risks inherent in the myelography procedure as arrhythmias and bradycardia during collection, transient apnea during contrast injection and seizures during recovery. Furthermore, deteriorating neurological signs, emesis, urinary retention and hyperthermia are other possible complications. Most of these complications are seen predominantly during cervical myelography compared to lumbar puncture because in the first exam, the contrast hardly reaches the brain and there is no risk of iatrogenic injury to the medulla oblongata. To minimize the neurotoxic effects, the ideal contrast should be radiopaque, water soluble, miscible with the cerebrospinal fluid (CSF), nontoxic and removed from the CSF by physiological processes. Iohexol contrast was used effectively, without neurotoxicity upon clinical evaluation while the volume used was sufficient to determine the injury site. The reported case demonstrated the possibility of performing lumbar myelography on Procyon cancrivorus effectively without significant complications or difficulties.
Keywords: wildlife; neurology; myelographic examination; Procyon cancrivoru